Evaluation of the efficacy of permethrin- and cypermethrin-based textile against taiga tick, Ixodes persulcatus - Zverev, Sergey A. (2023)
A comparison of the efficacy of permethrin- and cypermethrin-based textile against taiga ticks (Ixodes persulcatus) was carried out in a tick-borne viral encephalitis hotspot in the Irkutsk Region (Russia) using model samples of impregnated textiles. We demonstrated that permethrin- and cypermethrin-treated model samples have similar protective parameters in terms of maximum height reached by the tick when climbing up the treated textile (20.9-38.7 cm for cypermethrin, 27.6-39.3 cm for permethrin, depending on concentration) and knockdown time (i.e., the time until a female tick falls off the treated textile; 3.52-4.31 min for cypermethrin, 5.02-8.25 min for permethrin, depending on concentration). In contrast, when evaluating the 'biting speed' index (which is the ratio of the average attaching time of ticks contacting untreated textiles and ticks contacting treated textiles), it has been shown that permethrin-treated textiles accelerate biting. So, using permethrin-treated protective clothing against the taiga tick could be risky because it increases the likelihood of being bitten and thus getting infected. In contrast, cypermethrin-treated textiles appear to block the ability of ticks to attack warm-blooded animals and humans - after contact with cypermethrin-treated textiles none of the ticks attached to a rabbit. So cypermethrin-based textiles could be an alternative to permethrin for tick-bite protection clothing production if there is no toxic effect on humans of textile materials based on it.